2019
DOI: 10.1029/2018jd028640
|View full text |Cite
|
Sign up to set email alerts
|

Improving Land Surface Temperature Simulation in CoLM Over the Tibetan Plateau Through Fractional Vegetation Cover Derived From a Remotely Sensed Clumping Index and Model‐Simulated Leaf Area Index

Abstract: Parameterizations of fractional vegetation cover (FVC) in land surface models have important effects on simulations of surface energy budget, especially in arid and semiarid regions. This study uses a FVC scheme in which FVC is derived from leaf area index and a remotely sensed clumping index. The performance of the new scheme (SMFVC) is evaluated against Moderate Resolution Imaging Spectroradiometer (MODIS) land surface temperature (LST) and in situ soil temperature observations, together with two other FVC s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…The overestimation could be attributed to the uncertainty in meteorological forcing data, which was caused by insufficient meteorological stations (Wang et al, 2018) and the overestimated precipitation in the satellite‐based reanalysis data (e.g., TRMM) in the TI region (Tong et al, 2014). The uncertainty in the meteorological forcing data clearly affected the simulation of vegetation growth process in LSMs (Li et al, 2019), and eventually induced bias in GPP estimation. For example, the LAI derived from MODIS product was reported to be averagely 0.70 during 2000–2015 in the TI region (Tian et al, 2018), while the simulated LAI in the present study was larger than MODIS in the majority area of TI region (Figure S8), with the mean annual value being 0.94–0.98 and 1.38–1.47 from simulations with CRUF and CHNF data, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overestimation could be attributed to the uncertainty in meteorological forcing data, which was caused by insufficient meteorological stations (Wang et al, 2018) and the overestimated precipitation in the satellite‐based reanalysis data (e.g., TRMM) in the TI region (Tong et al, 2014). The uncertainty in the meteorological forcing data clearly affected the simulation of vegetation growth process in LSMs (Li et al, 2019), and eventually induced bias in GPP estimation. For example, the LAI derived from MODIS product was reported to be averagely 0.70 during 2000–2015 in the TI region (Tian et al, 2018), while the simulated LAI in the present study was larger than MODIS in the majority area of TI region (Figure S8), with the mean annual value being 0.94–0.98 and 1.38–1.47 from simulations with CRUF and CHNF data, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The overestimation could be attributed to the uncertainty in meteorological forcing data, which was caused by insufficient meteorological stations (Wang et al, 2018) and the overestimated precipitation in the satellite-based reanalysis data (e.g., TRMM) in the TI region (Tong et al, 2014). The uncertainty in the meteorological forcing data clearly affected the simulation of vegetation growth process in LSMs (Li et al, 2019), and eventually induced bias in GPP estimation. For example, the LAI derived from MODIS product was reported to be averagely 0.70 during…”
Section: Uncertainties In Estimating Gpp Across Chinamentioning
confidence: 99%
“…For example, based on the SRTM DEM, Zhang et al (2018) quantified the topographic effects of solar radiation on permafrost distribution in the northeast Tibetan Plateau and the simulated permafrost coverage increased by 8% when accounting for the impact of topographic shadows on surface energy budget. Li et al (2019) found that introducing MODISbased vegetation coverage data into the CoLM can reduce the warming biases in land surface temperature and surface soil temperature by ∼10°C in sparse vegetated areas in the Tibetan Plateau. assimilated the satellite microwavebased brightness temperature into SHAW model at the Amdo station in the central Tibetan Plateau, and found that the errors of simulated upper (0-2.58 m) soil temperature during wintertime reduced by 0.76°C.…”
Section: Integrate Remote Sensing Data With Process-based Models To Imentioning
confidence: 99%
“…LST derived from satellite remote sensing usually covers the entire TP, providing indispensable observed evidence over this data-sparse region. More specifically, LST products from the Moderate-Resolution Imaging Spectroradiometer (MODIS) are some of the best quality data ( Phan & Kappas, 2018 ; Wan et al, 2017 ; Wan, 2008 ; Wang et al, 2007 ), with high temporal frequency (four daily satellite overpasses) and spatial resolution (500 m), and have been trustworthily employed as a surrogate for or a supplementary source to LST changes since 2000 ( Jin & Mullens, 2012 ; Li et al, 2019a ; Zhang et al, 2014 ; Zhong et al, 2010 ). However, it is difficult to fully understand the physical processes and mechanisms of LST changes and to quantitatively analyze the contributions of various elements to the TP land surface energy and water changes only by relying on remote sensing data ( Chang et al, 2020 ; Ji, Yuan & Li, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…LSMs are based on physical mechanism and parameterization schemes, providing the possibility to further understand the mechanisms related to LST changes ( Hu et al, 2020 ; Orth et al, 2017 ; Trigo et al, 2015 ). LSMs usually generate LSTs that significant deviate from observations due to simplistic model representations of land surface heterogeneities, such as land surface cover type, soil properties, and soil moisture ( Johannsen et al, 2019 ; Li et al, 2019a ; Nogueira et al, 2020 ; Trigo et al, 2015 ; Wang et al, 2014 ). Many simulation results showed that the underestimation of LST and overestimation of sensible heat flux on bare-ground or sparsely vegetated surface during daytime are notable deficiencies in Noah LSM and Community Land Model version 3.5 (CLM3.5) ( Zeng, Wang & Wang, 2012 ; Zheng et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%